1999
DOI: 10.1002/(sici)1522-2594(199901)41:1<156::aid-mrm22>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of intrarenal macrophage infiltration in an experimental model of nephrotic syndrome

Abstract: The objective of this study was to use MR imaging to detect macrophage infiltration of the kidney after injection of ultrasmall superparamagnetic iron oxide (USPIO) particles in a rat model of experimental nephropathy. Ninety mol of USPIO were injected intravenously in 10 rats with nephropathy secondary to intravenous injection of 5 mg of puromycin aminonucleoside (PAN), and in 10 control rats. The signal intensity was measured in each kidney compartment before and 24 h after injection of the contrast agent. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…In the kidney, several previous animal experiments in rats demonstrated that in vivo targeting of intrarenal macrophages or activated mesangial cells by USPIO was possible [9][10][11][12][13]. Intensity of intrarenal signal change seemed to correlate well to the level of iron content, to the degree of macrophage infiltration, and to the degree of renal dysfunction.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…In the kidney, several previous animal experiments in rats demonstrated that in vivo targeting of intrarenal macrophages or activated mesangial cells by USPIO was possible [9][10][11][12][13]. Intensity of intrarenal signal change seemed to correlate well to the level of iron content, to the degree of macrophage infiltration, and to the degree of renal dysfunction.…”
Section: Introductionmentioning
confidence: 84%
“…Previous experimental studies on rats have shown that MR imaging, with intravenous infusion of USPIO, by showing a signal decrease in various kidney compartments, could serve as a non-invasive method to demonstrate intrarenal endocytic activity in various models of nephritides [9,11], including renal graft rejection [12] and acute renal failure following ischemia [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context of brain damages associated with inflammatory events, macrophage activity has been studied by MRI after USPIO infusion also in human patients suffering from stroke [92]. In vivo cellular MR imaging of USPIO-labeled macrophages has found successful applications in other animal models of disease, such as in kidney injuries (nephropathies) induced by a nephrotoxic drug (puromycin aminonucleoside) or in organ graft rejection (e.g., after renal allograft transplantation without any immunosuppressive drug) [3,93,94]. The accumulation of long-circulating USPIO in monocytes and macrophages recruited to atherosclerotic plaques has been demonstrated also in hyperlipidemic rabbits [95,96].…”
Section: Mri Monitoring Of Cells After Magnetic Labeling In Vivomentioning
confidence: 99%